2020
DOI: 10.1053/j.ajkd.2019.08.017
|View full text |Cite
|
Sign up to set email alerts
|

Association Between APOL1 Genotype and Need for Kidney Replacement Therapy in Patients Without Diabetes: Does Age Matter?

Abstract: Figure 1. Kaplan-Meier curves for cumulative KRT incidence among persons younger versus older than 54 years of age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
2

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 11 publications
0
2
2
Order By: Relevance
“…We found no evidence that age modified the associations of APOL1 genotype status with incident ESRD. These findings are in contrast with a recent study by Wei et al in AASK who reported a threshold age of 54 years, below which the APOL1 high‐risk genotypes were associated with a nearly 3‐fold higher HR of kidney replacement therapy and above which the APOL1 high‐risk genotypes were not associated with risk of kidney replacement therapy 27 . Importantly, participants of AASK consisted of African Americans with hypertension‐attributed CKD with baseline 123 I‐iothalamate GFR of 20 to 65 mL/min, 27‐29 whereas our study population was derived from a community‐based general population cohort with approximately 2% having a baseline eGFR below 60 mL/min/1.73 m 2 13,16 …”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…We found no evidence that age modified the associations of APOL1 genotype status with incident ESRD. These findings are in contrast with a recent study by Wei et al in AASK who reported a threshold age of 54 years, below which the APOL1 high‐risk genotypes were associated with a nearly 3‐fold higher HR of kidney replacement therapy and above which the APOL1 high‐risk genotypes were not associated with risk of kidney replacement therapy 27 . Importantly, participants of AASK consisted of African Americans with hypertension‐attributed CKD with baseline 123 I‐iothalamate GFR of 20 to 65 mL/min, 27‐29 whereas our study population was derived from a community‐based general population cohort with approximately 2% having a baseline eGFR below 60 mL/min/1.73 m 2 13,16 …”
Section: Discussioncontrasting
confidence: 99%
“…These findings are in contrast with a recent study by Wei et al in AASK who reported a threshold age of 54 years, below which the APOL1 high-risk genotypes were associated with a nearly 3-fold higher HR of kidney replacement therapy and above which the APOL1 high-risk genotypes were not associated with risk of kidney replacement therapy. 27 Importantly, participants of AASK consisted of African Americans with hypertension-attributed CKD with baseline 123 I-iothalamate GFR of 20 to 65 mL/min, [27][28][29] whereas our study population was derived from a community-based general population cohort with approximately 2% having a baseline eGFR below 60 mL/min/1.73 m 2 . 13,16 Our study shows that, even in older age, racial disparities in health outcomes continue to exist, and that many of these disparities, particularly in hospitalizations and all-cause mortality, are, in part, explained by social determinants of health.…”
Section: Discussionmentioning
confidence: 99%
“…This result is in disagreement with the study by kanji et al [30]. Moreover, this result was in agreement with the study by Wei et al that has demonstrated younger African American study of kidney disease and Hypertension (AASK) participants with high-risk genotype had the greatest KRT risk [34]. Genetic factors such as sickle cell trait have been investigated mostly among African Americans like of APOL1 genetic factors.…”
Section: оригінальні наукові роботиcontrasting
confidence: 48%
“…These studies revealed that genetic variants of APOL1 and non-muscle myosin heavy chain IIA (MHY9) in sickle cell disease (SCD) cause the progression of CKD to ESRD. The mean survival of patients with ESRD and SCD (sickle cell nephropathy) is estimated to be 4 years, even with dialytic treatment [34]. In the study by Masekoameng et al, they have not found a significant association between APOL1 and CKD in SCT patients, indicating that there is no evi-dence that SCT influences the relationship between APOL1 and CKD [35].…”
Section: оригінальні наукові роботиmentioning
confidence: 99%